Zoppoter Sportwoche : 8.-15. Juli 1923. (Zoppot : [s.n.], 1923)
Afisz z programem zawodów sportowych.
Keywords: Sport -- Polska -- Sopot -- 1900-1945 -- druki ulotne; Sopot (Polska) -- 1900-1945 -- druki ulotne